2010
DOI: 10.1088/1751-8113/43/9/095304
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of an entanglement by repetition of the resonant transmission of an ancilla qubit

Abstract: Abstract. A scheme for the extraction of entanglement in two noninteracting qubits (spins) is proposed. The idea is to make use of resonant transmission of ancilla qubit through the two fixed qubits, controlled by the entanglement in the scatterers. Repetition of the resonant transmission extracts the singlet state in the target qubits from their arbitrary given state. Neither the preparation nor the post-selection of the ancilla spin is required, in contrast to the previously proposed schemes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In conclusion, we have proposed a physical model for the systematic generation of N -partite states for quantum networking. The physics behind our idea has been clearly interpreted using the formalism of coupled angular momenta and the symmetries arising from an effective spin-spin scattering mechanism [5,6,17]. We have shown that, among other resources, our scheme is able to produce scalable multipartite singlet states for the performance of optimal telecloning.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In conclusion, we have proposed a physical model for the systematic generation of N -partite states for quantum networking. The physics behind our idea has been clearly interpreted using the formalism of coupled angular momenta and the symmetries arising from an effective spin-spin scattering mechanism [5,6,17]. We have shown that, among other resources, our scheme is able to produce scalable multipartite singlet states for the performance of optimal telecloning.…”
mentioning
confidence: 96%
“…The scheme enjoys many interesting features, such as robustness against static disorder, imperfect arrangements of RCs and phase noise [6,18]. Also, it does not require fine control of the interaction times or coupling strengths nor the preparation or postselection of the e's spin [6,17].…”
mentioning
confidence: 99%
“…In this paper we will first show that (1) all standard single qubit operations can be effected without any magnetic field through interactions of the form with the itinerant or “flying” non-equilibrium spin population while (2) two qubit operations can be implemented through separate interactions of the form and with the flying spin population . The latter process has been discussed earlier by several authors 11 12 13 14 15 16 17 18 19 20 21 and we draw on this work, but there is a key distinction with the present work as explained in the next section.…”
mentioning
confidence: 92%
“…A well-known major hindrance to the reliable accomplishment of quantum coherent operations stems from the noise that any required manipulation of quantum "hardware" inevitably introduces whenever a given task is to be achieved. Within this framework, an approach that is becoming increasingly popular is to encode the computational space in the (pseudo-) spin degrees of freedom of scattering particles and harness their interaction during the collision to process quantum information [2][3][4][5][6][7][8][9][10][11]. Scattering is indeed a typical phenomenon occurring under low-control conditions: Two or more particles are prepared so as to undergo scattering and eventually measured once this has concluded.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the accomplishment of QIP tasks, and more in general coherent operations, rather demanding. Indeed, while the works carried out along this line have targeted entanglement generation [2][3][4][5][6][7][8][9] and quantum state tomography [10], only the latest achievements have proved the possibility of performing a quantum algorithm such as teleportation [11]. The working principle behind this recent proposal, however, basically relies on a scatteringbased effective projective measurement of the singlet state of two remote scattering centers [11], that is, the same basic mechanism underpinning previous works that addressed entanglement generation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%